(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
The study begins with an analysis of the semantics of the Armenian word kapoyt, blue, taking into account its different uses in Armenian literature, e.g. its possible connection with natural elements (lakes, seas, sky, etc.), clothes, diseases, precious stones, and toponyms. Great attention has been paid to the metaphorical meanings of kapoyt in Armenian tradition, which are related with feelings such as envy, jealousy, and sorrow. The second part of the study deals with the colour blue as a mean of artistic expression. On the one hand, the symbolism of blue has been investigated through the reflection on the aesthetics of colour found in the works of some Armenian Christian authors of the Middle Ages. On the other, we analyse different types of pigment used by Armenian artists in different times and in different schools, according to the information of ancient handbooks on colour production, and on the basis of data concerning the trade in colouring matters.